The economics of ecosystems and biodiversity in business and enterprise - Bishop, Joshua (New York : Earthscan, 2012)
'This book is a further key output of TEEB (The Economics of Ecosystems and Biodiversity). It provides important new evidence of growing corporate concern about biodiversity loss and offers examples of how some leading companies are taking action to conserve biodiversity and to restore ecosystems. It reviews indicators and drivers of biodiversity loss and ecosystem decline, and shows how these present both risks and opportunities to business. It examines the changing preferences of consumers for nature-friendly products and services, and offers examples of how companies are responding. The book also describes recent initiatives to enable businesses to measure, value and report their impacts and dependencies on biodiversity and ecosystem services. A range of practical tools to manage biodiversity risks in business is reviewed, with examples of how some companies are using these tools to deliver added business value. It is shown how companies can take action to avoid, minimize and mitigate biodiversity and ecosystem service risks, using compensation ('offsets') where appropriate, based on the concept of Net Positive Impact. As a result they can grasp new business opportunities linked to biodiversity and ecosystem services, such as increasing cost-efficiencies, new products and new markets.The authors explore emerging business models that seek to deliver biodiversity benefits and ecosystem services on a commercial basis, the enabling frameworks needed to stimulate investment and entrepreneurship to realize such opportunities, and the obstacles that must be overcome. Overall, the book examines how businesses can align their actions in relation to biodiversity and ecosystem services with wider corporate social responsibility initiatives, including community engagement and poverty reduction'--
'This book is a further key output of TEEB (The Economics of Ecosystems and Biodiversity). It provides important new evidence of growing corporate concern about biodiversity loss and offers examples of how some leading companies are taking action to conserve biodiversity and to restore ecosystems'--
Includes bibliographical references and index.
Keywords: Environmental economics; Social responsibility of business; Biodiversity